Exotic searches in the Large Hadron Collider - Fernandez, Thiago Rafael T. [UNESP] (My University, 2014)
We present a selection of results of searches for physics beyond the standard model, reported by both the ATLAS and CMS collaborations, based on the data taken in the proton-proton collisions delivered by the LHC during 2012. The studies reported cover generic searches for new phenomena, as well as specific searches for new resonances, excited fermions, leptoquarks and vector-like quarks. In all searches covered in this report, no signs of physics beyond the standard model are observed.